Mellan praktik och disposition - En kvalitativ studie om instrumentlärares reflektioner kring undervisning i övningsmetodik - Lexander,Adam; Persson,Jonathan (2026)
Between practice and disposition examines how upper secondary instrumental music teachers in Sweden relate to practice methodology in their teaching. Drawing on our own experiences of instrumental instruction, as well as our perceptions of the relationship between curriculum documents and teachers’ pedagogical design of instrumental education, we found it meaningful to investigate the aforementioned phenomenon. We also perceive that music teachers’ backgrounds and values influence their teaching in complex and multifaceted ways, and this constitutes an additional focus of our investigation in relation to teachers’ approach to practice methodology. The aim of this study has been to illuminate how upper secondary teachers in music programmes, in a broader sense, relate to practice methodology. This broader question is articulated through the following research questions: How do upper secondary instrumental teachers describe their teaching of practice strategies to students? In what ways do teachers perceive their musical backgrounds to influence their teaching of practice methodology? How do teachers relate to curriculum formulations concerning practice methodology? What other factors do teachers identify as influencing the aforementioned teaching? The empirical material consists of semi-structured interviews with four upper secondary music teachers working within music programmes. To investigate how teachers relate their musical background with their teaching practice, Bourdieu’s theory of habitus was employed as an analytical framework. The empirical findings were related to previous research in our discussion chapter. The findings indicate that several teachers reflected on intrinsic and extrinsic motivation, the lesson as a model for practice, autonomy, and practice journals when discussing their approach to practice methodology. Furthermore, we found that teachers relate their formal and informal music-backgrounds to varying degrees within their pedagogical practice, and that teaching practice itself has shaped some of the participants habitus.
Keywords: didaktik; habitus; hysteresis; musik; styrdokument; övning; övningsmetodik; curriculum; didactics; music; practice; practice methodology; Utbildningsvetenskap; Musikpedagogik; Educational Science; Music Education